PPOK Eksaserbasi pada Laki-Laki Usia 41 tahun di Rumah Sakit Umum Daerah Cut Meutia Aceh Utara - Wirdatul Ulfia; Marliza Marliza (Pusat Riset dan Inovasi Nasional, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive chronic lung disease characterized by persistent airflow limitation that is not fully reversible. COPD is a leading cause of morbidity and mortality worldwide, strongly associated with smoking and environmental exposures. Acute exacerbations of COPD significantly worsen quality of life and increase hospitalization and mortality rates.Objective: To report a case of severe COPD exacerbation and review its management according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines.Methods: This descriptive observational case report describes a 41-year-old male patient with severe COPD exacerbation admitted to Cut Meutia General Hospital. Data were obtained from history taking, physical examination, diagnostic investigations, and evaluation of treatment response during hospitalization. Results: The patient presented with worsening dyspnea and productive cough. A history of heavy smoking and occupational dust exposure were identified as major risk factors. Physical examination revealed bilateral wheezing and prolonged expiration. Chest radiography supported the diagnosis of COPD. The patient was diagnosed with severe COPD exacerbation and treated with oxygen therapy, bronchodilators, systemic corticosteroids, antibiotics, and non-pharmacological measures. Gradual clinical improvement was observed. Conclusion: COPD exacerbation is a serious condition requiring prompt and comprehensive management. Early recognition of risk factors and guideline-based treatment can improve clinical outcomes and patient quality of life.